A longitudinal study of environmental and outdoor education: A cultural change. Issue 9 (24th September 2013) - Tal, Tali; Morag, Orly
Abstract In this case‐study, we present a longitudinal study of one elementary (grades 1–6) school's environmental education (EE) in order to understand the ways in which the school culture supports outdoor EE as a critical component of their science education program. The school, which was known for its school‐based EE curriculum that encompasses an intensive outdoor‐education component, has gone through changes in the staff, and the student population. Our study is aimed at understanding the current challenges of the school outdoor education, in light of its two decade tradition of environmental and outdoor education school‐based curriculum. We observed three field trips and interviewed the principal and teachers. Our critical analysis indicated key tensions regarding outdoor EE: (1) the place of the school's tradition in light of current staff's challenges and agenda; (2) power struggle between the EE teacher and the newer teachers in school; and (3) the separation between the EE program that was an integrative holistic program in the past, and the other fields taught in school. In conclusion, we argue that the main issue is the change in the school culture that reflects the changes the community went through. We suggest that the school should examine old assumptions and revise its EE curriculum in light of changes in the school social and physical environment and in accordance to development in the field of EE. © 2013 Wiley Periodicals, Inc. J Res Sci Teach 50: 1019–1046, 2013